The link between IPO underpricing and trading volume: Evidence from the Istanbul Stock Exchange - Aydin Yüksel; Asli Yüksel (The Journal of Entrepreneurial Finance and Business Ventures, 2006)
Recent evidence from U.S. markets shows that IPO underpricing is associated with high liquidity for issuing firms. One explanation given for this link is that IPO firms simultaneously decide on share retention and underpricing to maximize aftermarket liquidity. We use data from the Istanbul Stock Exchange (ISE) to provide international evidence. Our results do not support the argument that IPO firms use underpricing as a tool to make up the reduction in liquidity caused by higher share retention. We report that there is an asymmetric relationship between underpricing and trading volume in the short run. However, the positive link between short term volume and long term volume, which is shown to exist in U.S. markets, is missing in the ISE. Based on the explanations in prior research, we argue that the lack of persistency in initial broad ownership and/or investor interest may be the reason for the missing link.
Keywords: 650